Poverty lines and poverty in Suriname (General Bureau of Statistics ParamariboSR, 2001)
Presents the poverty lines methodology of the General Bureau of Standards, step by step, as well as the distributions of household income and household consumption. Contains poverty lines and poverty characteristics.
Additional copy located in the Statistics Sub-Programme